Mental Health Status and Suicidality Among Bisexual and Heterosexual Students at a Conservative Faith-Based University - Furst, Trevor (Journal of research on christian education, 2024)
This article examines the relationship between sexual orientation and mental health among bisexual students at a conservative faith-based university. Compared to heterosexual students, bisexual students were significantly more likely to have higher rates of anxiety, depression, suicide ideation and suicide attempts. Bisexual students were about 6 times more likely to experience anxiety and depression as well as about 9 times more likely to have attempted suicide. They were over 22 times more likely to have engaged in suicide ideation. The data strongly suggest the need for administrators at faith-based universities to be aware of these issues and offer support to bisexual students.